2015
DOI: 10.1016/j.jbiomech.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computed tomography-based finite element analysis predictions of femoral strength and stiffness depend on computed tomography settings

Abstract: The aim of the present study was to compare proximal femur strength and stiffness obtained experimentally with estimations from Finite Element Analysis (FEA) models derived from Quantitative Computed Tomography (QCT) scans acquired at two different scanner settings. QCT/FEA models could potentially aid in diagnosis and treatment of osteoporosis but several drawbacks still limit their predictive ability. One potential reason is that the models are still sensitive to scanner settings which could lead to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Although the study differentiated the predictive outcomes based on these two scanning protocols which combined voltage, current, and kernel, it did not consider the individual effects of these variables. The variations in measured HU values and estimated vBMD using phantoms could thus lead to incorrect estimations of bone strength and stiffness from FE models, as demonstrated in their study [21].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the study differentiated the predictive outcomes based on these two scanning protocols which combined voltage, current, and kernel, it did not consider the individual effects of these variables. The variations in measured HU values and estimated vBMD using phantoms could thus lead to incorrect estimations of bone strength and stiffness from FE models, as demonstrated in their study [21].…”
Section: Discussionmentioning
confidence: 92%
“…As this study demonstrates, the correlation between HU values and thereby estimated vBMD using a phantom will depend on the acquisition parameters. A previous study by Dragomir-Daescu et al showed predicted strength and stiffness of QCT/FEA models to differ between a high-and a lowresolution scanning protocol [21]. Although the study differentiated the predictive outcomes based on these two scanning protocols which combined voltage, current, and kernel, it did not consider the individual effects of these variables.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Techniques such as quantitative computed tomography (QCT)-based FEA have gained popularity due to their ability to incorporate both bone morphology and bone mechanical material properties. However, existing QCT-based FEA of the lower extremities (such as the tibia and the knee) generally has, by and large, been limited to biomechanical changes due to age-or disease-related bone degeneration and often uses idealized or highly simplified loading conditions (i.e., it only includes a few muscle forces) [18]. In contrast, exercise-related activities, such as walking while carrying loads, induce dynamic (time-varying) muscular and joint forces on the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that QCT/FEA predicted bone strength and stiffness can vary between models developed with high-resolution scans, used in the research community, and low-resolution scans, used in the clinical setting [12]. Furthermore, estimated volumetric bone mineral density (vBMD) values used for material properties' assignments in finite-element models measured from CT images were also shown to depend on scanning protocols [13].…”
Section: Introductionmentioning
confidence: 99%